Mindful activism autoethnographies of social justice communication for campus and community transformation - Tillmann, Lisa M., 1971-; Schoen, Steven (Professor of media); Norsworthy, Kathryn Louise (New York, NY : Routledge, 2022)
This collection immerses scholars of communication and related disciplines in narratives of and conversations about social-justice-focused activism. Through autoethnographic essays, Mindful Activism chronicles the authors' experiences as activist academics challenging and seeking to remedy injustices on campus and in local and global communities. Those experiences range from engaging in a single activist act to collaborating over many years with oppressed communities and social change groups. Building upon communication activism research and following a liberation-based transformative learning model, the book shows both activism in action and deep reflection on that activism. The authors re-experience activist experiences, draw out lessons, and invite readers to apply those to their own social justice endeavors. Mindful Activism also demonstrates how mindfulness supports activists in deepening their awareness and understanding of themselves, others, and social systems. This orientation increases the likelihood that activists will remain grounded enough to respond to injustice mindfully/effectively. The book will enrich courses on activism, social justice, dialogue, narrative inquiry, qualitative methods, autoethnography, and general graduate studies, and will resonate with scholars committed to building a more equitable and just world.
Introduction: Birthing the book / Kathryn Norsworthy, Lisa M. Tillmann, & Steven Schoen -- Sitting out "The star-spangled banner" / Lisa M. Tillmann, Kathryn Norsworthy, & Steven Schoen -- Of all days : critical pedagogy outside the classroom / Lisa M. Tillmann, Kathryn Norsworthy, & Steven Schoen -- Queer border crossings / Kathryn Norsworthy, Lisa M. Tillmann, & Steven Schoen -- Wind and winding roads : friendship amidst indefinite confinement / Lisa M. Tillmann, Jeffrey Holmgren, Kathryn Norsworthy, & Steven Schoen -- "Say it ain't so" : protecting a nondiscrimination policy from appropriated diversity / Steven Schoen, Lisa M. Tillmann, & Kathryn Norsworthy -- Conclusion: Mindful activists debrief mindful activism / Lisa M. Tillmann, Steven Schoen, & Kathryn Norsworthy.
Keywords: SOCIAL SCIENCE / Essays; EDUCATION / Higher; Social justice and education -- United States; College teaching -- Social aspects -- United States; Critical pedagogy -- United States; Transformative learning -- United States; College teachers -- Political activity -- United States; College teachers -- United States -- Anecdotes; Communication in education -- United States; Communication in social action -- United States; Universities and colleges -- United States -- Sociological aspects